Pressure kicks in the NFL: An archival exploration into the deployment of timeouts and other environmental correlates - Goldschmeid, N.; Nankin, M.; Cafri, G. (The Sport Psychologist, 2010)
Icing is a common strategy used in American football during the last moments of a close game when a coach may ask for a time-out to allow an opposing kicker, who is about to attempt a decisive field-kick, an extended period of time possibly to contemplate the negative outcomes if he fails to score (i.e., rumination). Using archival data of pressure kicks from six consecutive National Football League seasons (2002-2008), a mixed-effects hierarchical linear model was applied. It was found that icing was successful in reducing scoring while other environmental factors such as experience, game location or game score were not associated with conversion success. In a secondary analysis it was demonstrated that if a time-out before the pressure kick is requested by the coaches of the kicking team, kickers are not subjected to the debilitating effects of icing. Theoretical and applied implications are also discussed.